Rectal gastrointestinal stromal tumor with metastasis to the penis: Case report and review of literature. (2016) - Carlson, Jacob; Alobuia, Wilson; Mizell, Jason
Highlights: The first reported case of a rectal GIST with metastasis to the penis is documented by this report. The primary cancer was treated with neoadjuvant chemotherapy and abdominoperineal resection. Biopsies of lesions identified on follow-up imaging were consistent with metastatic GIST. Metastasectomy and adjuvant chemotherapy have been utilized to help prolong survival. Abstract: We report the case of a 51-year-old gentleman with previously diagnosed gastrointestinal stromal tumor (GIST) of the rectum with metastasis to the penis. The patient underwent abdominoperineal resection of the primary tumor with negative margins and completed a three-year course of imatinib mesylate (Gleevec). Forty months after resection of his rectal tumor, the patient presented to his urologist with worsening testicular pain, mild lower urinary tract obstructive symptoms, and nocturia. A pelvic MRI revealed the presence of an ill-defined mass in the right perineum extending from the base of the penis to the penoscrotal junction. Biopsy of this mass was consistent with metastatic GIST. To our knowledge, this is the first report of metastatic GIST to the penis.